Plasmodium knowlesi gene expression differs in ex vivo compared to in vitro blood-stage cultures - Lapp, Stacey A (2015)
Background: Plasmodium knowlesi is one of five Plasmodium species known to cause malaria in humans and can result in severe illness and death. While a zoonosis in humans, this simian malaria parasite species infects macaque monkeys and serves as an experimental model for in vivo, ex vivo and in vitro studies. It has underpinned malaria discoveries relating to host-pathogen interactions, the immune response and immune evasion strategies. This study investigated differences in P. knowlesi gene expression in samples from ex vivo and in vitro cultures. Methods: Gene expression profiles were generated using microarrays to compare the stage-specific transcripts detected for a clone of P. knowlesi propagated in the blood of a rhesus macaque host and then grown in an ex-vivo culture, and the same clone adapted to long-term in vitro culture. Parasite samples covering one blood-stage cycle were analysed at four-hour intervals. cDNA was generated and hybridized to an oligoarray representing the P. knowlesi genome. Two replicate experiments were developed from in vitro cultures. Expression values were filtered, normalized, and analysed using R and Perl language and applied to a sine wave model to determine changes in equilibrium and amplitude. Differentially expressed genes from ex vivo and in vitro time points were detected using limma R/Bioconductor and gene set enrichment analysis (GSEA). Results: Major differences were noted between the ex vivo and in vitro time courses in overall gene expression and the length of the cycle (25.5 hours ex vivo; 33.5 hours in vitro). GSEA of genes up-regulated ex vivo showed an enrichment of various genes including SICAvar, ribosomal- associated and histone acetylation pathway genes. In contrast, certain genes involved in metabolism and cell growth, such as porphobilinogen deaminase and tyrosine phosphatase, and one SICAvar gene, were significantly up-regulated in vitro. Conclusions: This study demonstrates how gene expression in P. knowlesi blood-stage parasites can differ dramatically depending on whether the parasites are grown in vivo, with only one cycle of development ex vivo, or as an adapted isolate in long-term in vitro culture. These data bring emphasis to the importance of studying the parasite, its biology and disease manifestations in the context of the host.